Nonmedical Costs in Patients Receiving Oral Cancer Surgery: Interim Analysis from the COOLS Trial. (23rd August 2013) - Cromwell, Ian; Cressman, Sonya; Poh, Catherine; Rosin, Miriam P.; Durham, Scott; Peacock, Stuart
Abstract : Objectives: 1) Describe the non‐medical financial burden experienced by early‐stage oral cancer patients. 2) Analyze constituent costs and discover relevant potential policy levers. Methods: The pan‐Canadian Optically‐guided Oral Lesions Surgical (COOLS) Trial is a multi‐center randomized controlled trial evaluating a novel surgical staging method for the treatment of early‐stage oral cancer. A survey of 209 participants collected data at baseline, 3 months, and 12 months after surgery on time taken away from work and expenses paid out of pocket. Results: Participants were generally able to return to work following surgery, albeit with a slight reduction in self‐reported ability to work. Very few patients needed to take time off work or changed their working status (ie, going on medical leave, retiring) following their surgery (n = 4; 10 weeks; range = 5 ‐ 146 days). A majority of trial participants reported out‐of‐pocket spending at baseline (n = 128; $64.55; 95% confidence interval [CI] $40 ‐ $88), 3 months (n = 108; $82.44; 95% CI $56 ‐ $109), and 12 months after surgery (n = 51; $65.01; 95% CI $13 ‐ $117). Most out of pocket expenses were non‐reimbursed travel costs. Conclusions: Oral cancer, when treated at an early stage, was not generally a barrier to returning to work in our participant sample. Moderate out‐of‐pocket expenditure was observed in a large number of patients, mostly related to travelling. Programs to defray the cost of travel may be helpful in many cases, but broader evidence is needed.